Comparison of Relativistic Microburst Activity Seen by SAMPEX With Ground‐Based Wave Measurements at Halley, Antarctica. Issue 2 (22nd February 2018) - Douma, Emma; Rodger, Craig J.; Clilverd, Mark A.; Hendry, Aaron T.; Engebretson, Mark J.; Lessard, Marc R.
Abstract: Relativistic electron microbursts are a known radiation belt particle precipitation phenomenon; however, experimental evidence of their drivers in space have just begun to be observed. Recent modeling efforts have shown that two different wave modes (whistler mode chorus waves and electromagnetic ion cyclotron (EMIC) waves) are capable of causing relativistic microbursts. We use the very low frequency/extremely low frequency Logger Experiment and search coil magnetometer at Halley, Antarctica, to investigate the ground‐based wave activity at the time of the relativistic microbursts observed by the Solar Anomalous Magnetospheric Particle Explorer. We present three case studies of relativistic microburst events, which have one or both of the wave modes present in ground‐based observations at Halley. To extend and solidify our case study results, we conduct superposed epoch analyses of the wave activity present at the time of the relativistic microburst events. Increased very low frequency wave amplitude is present at the time of the relativistic microburst events, identified as whistler mode chorus wave activity. However, there is also an increase in Pc1–Pc2 wave power at the time of the relativistic microburst events, but it is identified as broadband noise and not structured EMIC emissions. We conclude that whistler mode chorus waves are, most likely, the primary drivers of relativistic microbursts. However, case studies confirm the potential of EMIC waves as an occasional driver of relativistic microbursts. Key Points: Case studies of relativistic microbursts with EMIC and/or chorus waves occurring are presented Statistically, there is an increase in VLF wave amplitude at the time of relativistic microbursts, consistent with chorus Statistically, there is no increase in EMIC activity at the time of relativistic microbursts